LEADERSHIP STRATEGY IN IMPROVING THE QUALITY OF PAUD MANAGEMENT IN MUSI RAWAS DISTRICT, SOUTH SUMATERA - Dwi Puji Hastuti; Siti Inganah (RADJA PUBLIKA, 2025)
Overall, this study confirms that leadership strategies play a crucial role in improving the quality of PAUD management. The implementation of transformational, participatory leadership, focus on professional development, effective communication, and efficient and accountable resource management are key factors that contribute to the creation of a quality PAUD environment that is conducive to early childhood development. This study aims to fill the gap in leadership strategies in an institution and contribute to the understanding of effective leadership practices in improving the quality of PAUD management. The research was conducted in Musi Rawas Regency, South Sumatra with the research subjects being the Principals of TK Aisyiyah 8 Musi Rawas. The things explored in this study were leadership strategies in improving the quality of Early Childhood Education management. The research techniques used in this study were observation, document studies, and in-depth interviews. The data analysis used was descriptive analysis, namely an analysis that provides an overview of the things that have been studied. While the method used in this study was a qualitative analysis method. The analysis was carried out through several stages, namely: data collection, data reduction, data display, and conclusion drawing. Meanwhile, to obtain data validity, the researcher used triangulation techniques, namely by using various methods to collect the same data from various data sources. The data was obtained from the TK PAUD Aisyiyah Bustanul Athfal institution, Musi Rawas Regency, South Sumatra Province In Musi Rawas Regency, Tugumulyo District, the Aisyiyah Bustanul Athfal Teachers Association has strategies in its leadership, namely by conducting parenting activities, regular meetings every 2-3 months with the Muhammadiyah Regional Leadership, Aisyiyah Regional Leadership, IGABA (Head, Educators, Educators), holding joint activities, namely holding Hajj Manasik for Early Childhood, Learning outside of school, namely in the Library, Police Station, learning with the Outing Class practice method and aligning the vision, mission and goals of the school, so that the achievement of the learning objectives provided is in accordance with the goals and ideals of the Aisyiyah Muhammadiyah Organization itself so that it can be achieved adequately for the progress of the nation and provide quality Early Childhood Education.